Polarizing plate with adhesive layer and display device

CN122953428APending Publication Date: 2026-10-20FUJIFILM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202580021785.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-21
Filing Date
2025-03-21
Publication Date
2026-10-20

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention provides a polarizer with an adhesive layer that suppresses curling and a display device. The polarizer with an adhesive layer of this invention comprises: a polarizer having, in sequence, a protective film, a polarizer, a positive A plate, and a positive C plate; and an adhesive layer disposed on the positive C plate side of the polarizer, wherein the positive A plate is a layer obtained by curing a polymerizable liquid crystal compound, and the thickness of the positive C plate is 20.0–70.0 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polarizer with an adhesive layer and a display device. Background Technology

[0002] Optical anisotropic layers formed using liquid crystal compounds are applied in various fields, including displays.

[0003] For example, Patent Document 1 discloses a method for manufacturing a polarizer including a polarizer and an optical anisotropy layer.

[0004] Previous technical documents Patent documents Patent Document 1: International Publication No. 2023 / 276611 Summary of the Invention

[0005] The technical problem to be solved by the invention As one form of polarizer, it is desirable to configure an adhesive layer on one surface of the polarizer to use it as a polarizer with an adhesive layer.

[0006] The inventors fabricated a polarizer with an adhesive layer by depositing an adhesive layer on one surface of the polarizer disclosed in Patent Document 1. As a result, they found that the polarizer with the adhesive layer curled up, making it difficult to adhere to the substrate.

[0007] In view of the above, the objective of the present invention is to provide a polarizer with an adhesive layer in which curling is suppressed.

[0008] Furthermore, another objective of the present invention is to provide a display device.

[0009] means for solving technical problems The inventors have discovered that the above-mentioned problems can be solved by the following structure.

[0010] (1) A polarizer with an adhesive layer, comprising: A polarizer, comprising a protective film, a polarizer, a positive A plate, and a positive C plate, in sequence; and An adhesive layer is disposed on the positive C-plate side of the polarizer, wherein, The positive A plate is a layer obtained by curing a polymerizable liquid crystal compound, and the thickness of the positive C plate is 20.0–70.0 μm.

[0011] (2) The polarizer with adhesive layer according to (1), wherein when the polarizer with adhesive layer is bonded to the glass substrate by adhesive and the bonded polarizer with adhesive layer is subjected to a cross-cut test of 100 grids, the number of grids peeled off is 50 or less.

[0012] (3) The polarizer with adhesive layer according to (1) or (2), wherein the retardation of the positive C plate in the thickness direction at a wavelength of 550 nm is -100 to -30 nm.

[0013] (4) A polarizer with an adhesive layer according to any one of (1) to (3), wherein the positive C plate comprises a polymer film.

[0014] (5) The polarizer with adhesive layer according to (4), wherein the polymer film is a cellulose acylated film.

[0015] (6) The polarizer with adhesive layer according to (4) or (5), wherein the polymer film has an in-plane retardation of less than 10 nm at a wavelength of 550 nm.

[0016] (7) A polarizer with an adhesive layer according to any one of (4) to (6), wherein the polymer film has a thickness retardation of -100 to 30 nm at a wavelength of 550 nm.

[0017] (8) A polarizer with an adhesive layer according to any one of (4) to (7), wherein the positive C plate comprises a vertically aligned liquid crystal layer and a polymer film.

[0018] (9) The polarizer with adhesive layer according to (8), wherein the vertically oriented liquid crystal layer comprises a crosslinker biased to the side of the polymer film.

[0019] (10) A polarizer with an adhesive layer according to (8) or (9), wherein the vertically oriented liquid crystal layer is a layer formed using a composition comprising a liquid crystal compound and a crosslinking polymer having hydroxyl groups.

[0020] (11) A polarizer with an adhesive layer according to any one of (8) to (10), wherein the vertically oriented liquid crystal layer contains a photoisomerizing compound on the surface opposite to the polymer film side.

[0021] (12) A polarizer with an adhesive layer according to any one of (1) to (11), wherein the angle between the absorption axis of the polarizer and the in-plane slow axis of the positive A plate is 45 ± 10°. The in-plane retardation of the positive A plate at a wavelength of 550 nm is 120–170 nm.

[0022] (13) The polarizer with an adhesive layer according to any one of (1) to (12), wherein the polarizer and the positive A plate are laminated via a polyvinyl alcohol adhesive.

[0023] (14) A polarizer with an adhesive layer according to any one of (1) to (13), wherein the positive A plate is a layer obtained by curing a composition comprising a polymeric liquid crystal compound and a polymer having a group represented by formula (1).

[0024] (15) A polarizer with an adhesive layer according to any one of (1) to (12), wherein the polarizer and the positive A plate are stacked via an adhesive layer formed by curing an ultraviolet-curable adhesive.

[0025] (16) A polarizer with an adhesive layer according to any one of (8) to (11), wherein the polymer film includes region A containing a component derived from a liquid crystal compound contained in a vertically oriented liquid crystal layer, and the thickness of region A is 20 to 200 nm.

[0026] (17) A display device having a polarizer with an adhesive layer as described in any one of (1) to (16).

[0027] Invention Effects According to the present invention, it is possible to provide a polarizer with an adhesive layer in which curling is suppressed.

[0028] Furthermore, according to the present invention, a display device can also be provided. Attached Figure Description

[0029] Figure 1 This is a diagram conceptually illustrating an example of a polarizer with an adhesive layer according to the present invention. Detailed Implementation

[0030] The present invention will now be described in detail.

[0031] The following description of the constituent elements is sometimes based on representative embodiments and specific examples, but the present invention is not limited to such embodiments.

[0032] In addition, in this specification, the numerical range indicated by “~” refers to the range included by taking the values ​​recorded before and after “~” as the lower limit and upper limit values.

[0033] In this specification, "absorption axis" refers to the polarization direction in which the in-plane absorbance is greatest when incident on linearly polarized light. Furthermore, "in-plane slow axis" refers to the direction in which the in-plane refractive index is greatest.

[0034] Furthermore, in this specification, Re(λ) and Rth(λ) represent the in-plane retardation and thickness retardation at wavelength λ, respectively. Unless otherwise specified, wavelength λ is 550 nm.

[0035] In this invention, Re(λ) and Rth(λ) are values ​​obtained by measurement at wavelength λ using an AxoScan (manufactured by Axometrics). The film thickness (d) can be calculated by inputting the average refractive index ((nx+ny+nz) / 3) and the film thickness (d) into the AxoScan. In-plane slow axis direction (°); Re(λ) = R0(λ) Rth(λ)=((nx+ny) / 2-nz)×d Additionally, R0(λ) represents the value calculated by AxoScan, but refers to Re(λ).

[0036] Furthermore, in this specification, the refractive indices nx, ny, and nz are measured using an Abbe refractometer (NAR-4T, manufactured by ATAGO CO.,LTD.) and a sodium lamp (λ=589nm) as the light source. Moreover, when measuring wavelength dependence, measurements can be performed using a multi-wavelength Abbe refractometer DR-M2 (manufactured by ATAGO CO.,LTD.) in combination with an interference filter.

[0037] Furthermore, values ​​from the polymer handbook (JOHN WILEY & SONS, INC) and various optical film product catalogs can be used. The following are examples of the average refractive index values ​​for major optical films: cellulose acylate (1.48), cycloolefin polymer (1.52), polycarbonate (1.59), polymethyl methacrylate (1.49), and polystyrene (1.59).

[0038] In this specification, the A-board and C-board are defined as follows.

[0039] There are two types of A-plates: positive A-plates and negative A-plates. When the refractive index along the slow axis (where the in-plane refractive index is at its maximum) is set as nx, the refractive index along the direction orthogonal to the slow axis is set as ny, and the refractive index along the thickness direction is set as nz, the positive A-plate satisfies equation (A1), while the negative A-plate satisfies equation (A2). Furthermore, the Rth of the positive A-plate exhibits a positive value, while the Rth of the negative A-plate exhibits a negative value.

[0040] Equation (A1) nx>ny≈nz Equation (A2) ny<nx≈nz Furthermore, the aforementioned “≈” not only includes cases where the two are completely identical, but also cases where they are substantially identical. “Substantially identical” includes, for example, cases where (ny-nz)×d (where d is the film thickness) is -10 to 10 nm, preferably -5 to 5 nm, and cases where (nx-nz)×d is -10 to 10 nm, preferably -5 to 5 nm, and cases where (nx-nz)×d is -10 to 10 nm, preferably -5 to 5 nm, and cases where nx≈nz.

[0041] There are two types of C-plates: positive C-plates and negative C-plates. Positive C-plates satisfy the relationship in equation (C1), while negative C-plates satisfy the relationship in equation (C2). Furthermore, the Rth of a positive C-plate is negative, while the Rth of a negative C-plate is positive.

[0042] Equation (C1) nz>nx≈ny Equation (C2) nz<nx≈ny Furthermore, the aforementioned “≈” includes not only cases where the two are exactly the same, but also cases where they are substantially the same. “Substantially the same” means, for example, that even when (nx-ny)×d (where d is the thickness of the film) is 0 to 10 nm, and preferably 0 to 5 nm, it is included in “nx≈ny”.

[0043] One characteristic of the polarizer with adhesive layer of the present invention is the use of a positive C-plate of a specified thickness.

[0044] One of the main reasons why conventional polarizers with adhesive layers are prone to curling is that the positive A-plate in these polarizers is a layer obtained by curing a polymeric liquid crystal compound. It is believed that because the positive A-plate is a layer obtained by curing a polymeric liquid crystal compound, residual stress caused by curing shrinkage during polymerization results in the polarizer as a whole being prone to curling. Therefore, in this invention, curling is suppressed by adjusting the thickness of the positive C-plate within a specified range.

[0045] Figure 1 An example of a polarizer with an adhesive layer according to the present invention is shown.

[0046] like Figure 1 As shown, the polarizer 10 with adhesive layer sequentially includes a polarizer 12 and an adhesive layer 22. The polarizer 12 sequentially includes a protective film 14, a polarizer 16, a positive A plate 18, and a positive C plate 20. (As shown...) Figure 1 As shown, the adhesive layer 22 is disposed on the positive C-plate 20 side of the polarizer 12. More specifically, the adhesive layer 22 is disposed on the surface of the positive C-plate 20 side of the polarizer 12.

[0047] Furthermore, the positive C plate 20 has a vertically oriented liquid crystal layer 24 and a polymer film 26.

[0048] exist Figure 1 In this process, each layer is directly adjacent to other layers, but as will be described later, they can also be stacked via other layers (e.g., sealing layers).

[0049] The components included in the polarizer 10 with adhesive layer will be described in detail below.

[0050] <Protective film> The protective film is a film that protects the polarizer.

[0051] The structure of the protective film is not particularly limited; for example, it can be a transparent support or a hard coating, or a laminate of a transparent support and a hard coating.

[0052] In addition, in this specification, "transparent" means that the transmittance of visible light is 60% or more, preferably 80% or more, and more preferably 90% or more. The upper limit is not particularly limited, but in most cases it is less than 100%.

[0053] As a transparent support, known transparent supports (preferably transparent resin supports) can be cited. As materials forming the transparent support, examples include cellulose-based resins (hereinafter also referred to as cellulose acylates), represented by triacetylcellulose; norbornene-based resins (ZEONEX and ZEONOR manufactured by Zeon Corporation, ARTON manufactured by JSRCORPORATION, etc.); acrylic resins; polyester resins; and polystyrene-based resins. Among these, cellulose-based resins or norbornene-based resins are preferred, and cellulose-based resins are more preferred.

[0054] In addition, norbornene-based resins refer to resins that have a norbornene backbone. More specifically, examples include cyclic olefin polymers (COPs) and cyclic olefin copolymers (COCs).

[0055] As a hard coating, known layers can be used, such as layers obtained by polymerizing and curing multifunctional monomers.

[0056] The thickness of the protective film is not particularly limited, but from the viewpoint of reducing the thickness of the polarizer, it is preferably 40 μm or less, more preferably 25 μm or less. The lower limit is not particularly limited, but it is more common to find thicknesses of 10 μm or more.

[0057] <Polarizer> A polarizer is any component that can convert natural light into specific linearly polarized light; for example, an absorption polarizer can be cited.

[0058] There are no particular restrictions on the type of polarizer; commonly used polarizers can be used, such as iodine-based polarizers, dye-based polarizers utilizing dichroic substances, and polyene-based polarizers. Iodine-based and dye-based polarizers are usually made by adsorbing iodine or dichroic dyes onto polyvinyl alcohol and then stretching it.

[0059] As a polarizer, a polarizer formed by using a composition comprising a dichroic substance and a liquid crystal compound having polymerizable groups is also preferred.

[0060] Dichroic substances are not particularly limited and can include visible light absorbing substances (dichroic pigments), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet light absorbing substances, infrared light absorbing substances, nonlinear optical substances, carbon nanotubes and inorganic substances (such as quantum rods), etc., and previously known dichroic substances (dichroic pigments) can be used.

[0061] The transmittance of the polarizer's visibility correction unit is not particularly limited, but from the viewpoint of achieving better results with this invention, it is preferably 42% or higher, more preferably 43% or higher. The upper limit is not particularly limited, but is preferably 48% or lower.

[0062] In addition, the visibility-corrected monomer transmittance is calculated using the following method.

[0063] For the polarizer, a spectrophotometer with an integrating sphere (“V7100” manufactured by JASCO Corporation) is used to measure the transmittance (T1) along the absorption axis and the transmittance (T2) in the direction orthogonal to the absorption axis in the wavelength range of 380–780 nm. Based on the following formula, the single-cell transmittance in each wavelength is calculated.

[0064] Monomer transmittance (%) = (T1 + T2) / 2 For the obtained single-cell transmittance, visibility correction is performed according to the 2-degree field of view (C light source) of JIS Z 8701:1999 "Color display method - XYZ color system and X10Y10Z10 color system", and the visibility-corrected single-cell transmittance is calculated.

[0065] The thickness of the polarizer is not particularly limited, but from the viewpoint of enabling the polarizer to be thinner, it is preferably 40 μm or less, more preferably 25 μm or less. The lower limit is not particularly limited, but it is mostly 5 μm or more.

[0066] <Form A Board> The definition of the positive A plate is as described above.

[0067] The in-plane delay Re(550) of the positive A plate at a wavelength of 550 nm is not particularly limited, but from the viewpoint that the polarizer of the present invention is more superior as a circular polarizer, it is preferably 100 to 180 nm, more preferably 120 to 170 nm, and even more preferably 130 to 150 nm.

[0068] The positive A-plate can display positive wavelength dispersion (the characteristic that the in-plane delay decreases as the measurement wavelength increases) and negative wavelength dispersion (the characteristic that the in-plane delay increases as the measurement wavelength increases). Furthermore, it is preferable to display both positive and negative wavelength dispersion in the visible light region.

[0069] The positive A plate is a layer obtained by curing a polymeric liquid crystal compound.

[0070] From the viewpoint that the polarizer of the present invention is superior as a circular polarizer, a layer obtained by curing a horizontally oriented polymeric rod-shaped liquid crystal compound is preferred.

[0071] Furthermore, the horizontal orientation of the polymeric rod-shaped liquid crystal compound refers to the parallelism of its long axis to the main surface of the positive A-plate. However, strict parallelism is not required; the angle between the long axis of the polymeric rod-shaped liquid crystal compound and the main surface of the positive A-plate is preferably within the range of 0 ± 20°, and more preferably within the range of 0 ± 10°.

[0072] Polymerizable liquid crystal compounds are liquid crystal compounds that have polymerizable groups.

[0073] As a polymerizable liquid crystal compound, known compounds can be used.

[0074] Examples of polymerizable rod-shaped liquid crystal compounds include, for instance, the compounds described in claim 1 of Japanese Patent Application Publication No. 11-513019 and paragraphs 0026 to 0098 of Japanese Patent Application Publication No. 2005-289980.

[0075] In this specification, the type of polymerizable group is not particularly limited, but is preferably a functional group capable of addition polymerization, more preferably a polymerizable olefinic unsaturated group or a cyclic polymerizable group, and even more preferably (meth)acryloyl, vinyl, styrene or allyl.

[0076] The positive A plate is preferably a layer formed by fixing a polymeric rod-shaped liquid crystal compound through polymerization, and more preferably a layer formed by fixing a horizontally oriented polymeric rod-shaped liquid crystal compound through polymerization.

[0077] Furthermore, in this specification, the "fixed" state refers to the state in which the orientation of the liquid crystal compound is maintained. Specifically, the preferred state is one in which the layer does not flow under normal conditions of 0°C to 50°C, or under more severe conditions of -30°C to 70°C, and its orientation morphology does not change due to external fields or forces, thus stably and continuously maintaining a fixed orientation morphology.

[0078] The angle between the in-plane slow axis of the positive A plate and the absorption axis of the polarizer is not particularly limited. From the viewpoint that the polarizer of the present invention is superior as a circular polarizer, it is preferred to be in the range of 45±10° (35 to 55°).

[0079] The thickness of the positive A plate is not particularly limited, but is preferably less than 10 μm, and more preferably 0.1 to 5.0 μm.

[0080] Furthermore, the thickness of the A-plate refers to its average thickness. This average thickness is obtained by measuring the thickness at any five or more points on the A-plate and then taking the arithmetic mean of these measurements. The thickness can be measured, for example, using a reflective spectrophotometer FE3000.

[0081] The positive A plate is preferably a layer obtained by curing a composition containing a polymeric liquid crystal compound and a polymer having a group represented by formula (1).

[0082] Polymerizable liquid crystal compounds are as described above.

[0083] By using a polymer having groups represented by formula (1), the adhesion between the positive A plate and the PVA adhesive disposed adjacent to the positive A plate is improved.

[0084] Equation (1) -B- (OR x1 )2 R x1 Each of the two R groups independently represents a hydrogen atom, a substituted or unsubstituted aliphatic hydrocarbon group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group. x1 They can be linked together via alkylene linkages, arylene linkages, or combinations thereof.

[0085] Examples of substituted or unsubstituted aliphatic hydrocarbon groups include alkyl, alkenyl, or ynyl groups, which may have substituents.

[0086] Examples of substituted or unsubstituted aryl groups include phenyl, naphthyl, anthraceneyl, phenanthryl, indene, acenaphthene, fluorenyl, and pyrene.

[0087] As a substituted or unsubstituted heteroaryl group, an example of a heteroaryl group obtained by removing a hydrogen atom from a heteroaryl ring containing one or more heteroatoms selected from the group consisting of nitrogen, oxygen and sulfur atoms can be cited.

[0088] The polymer described above preferably contains repeating units having groups represented by formula (1).

[0089] As a repeating unit having a group represented by formula (1), a repeating unit represented by formula (X) can be cited.

[0090] [Chemical Formula 1] R x1 The definition is as described above.

[0091] R x2 and R x3 Each can be used to represent a hydrogen atom or an alkyl group independently.

[0092] The number of carbon atoms in alkyl groups is not particularly limited, but is preferably 1 to 18.

[0093] Alkyl groups can be any of the following structures: straight-chain, branched, or cyclic.

[0094] R x4 It represents a hydrogen atom or a substituent.

[0095] Examples of substituents include hydroxyl, alkyl, alkenyl, and aryl.

[0096] L X It indicates a divalent linker.

[0097] The divalent linking group is not particularly limited, and examples include alkylene (preferably alkylene with 1 to 20 carbon atoms), arylene, -O-, -S-, -CO-, -SO-, -SO2-, and -NR. a - Or a divalent linking group formed by combining multiple of them. R a It represents a hydrogen atom or an alkyl group.

[0098] Among them, the preferred divalent linking group is -alkylene-O-(arylene-CO-O). nx -Asaryl-. nx represents an integer from 0 to 2.

[0099] The content of repeating units having groups represented by formula (1) is preferably 5 to 30% by mass relative to all repeating units contained in the polymer.

[0100] The polymer described above may contain repeating units other than repeating units having a group represented by formula (1).

[0101] For example, a polymer may contain repeating units having groups represented by formula (2).

[0102] [Chemical Formula 2] R y1 ~R y3 Each can be independently represented as alkyl, alkenyl, aryl, or alkylene aryl.

[0103] Examples of alkyl groups include straight-chain alkyl groups with 1 to 18 carbon atoms, branched alkyl groups with 3 to 18 carbon atoms, and cyclic alkyl groups.

[0104] Examples of alkenyl groups include those with 2 to 12 carbon atoms.

[0105] Aryl groups with 6 to 12 carbon atoms can be cited as examples. Specifically, phenyl, α-methylphenyl, and naphthyl groups can be cited.

[0106] Examples of alkylene aryl groups include those with 7 to 30 carbon atoms.

[0107] The polymer described above preferably contains repeating units having groups represented by formula (2).

[0108] As a repeating unit having a group represented by formula (2), a repeating unit represented by formula (Y) can be cited.

[0109] [Chemical Formula 3] R y1 ~R y3 The definition is as described above.

[0110] R y4 and R y5 Alkyl groups are represented independently.

[0111] The number of carbon atoms in alkyl groups is not particularly limited, but is preferably 1 to 18.

[0112] Alkyl groups can be any of the following structures: straight-chain, branched, or cyclic.

[0113] R y6 It represents a hydrogen atom or a substituent.

[0114] Examples of substituents include hydroxyl, alkyl, alkenyl, and aryl.

[0115] L y1 It indicates a single bond or an alkylene group having 1 to 6 carbon atoms.

[0116] L y2 This indicates a ny+1 valence linker that does not have a fluorine atom.

[0117] As L y2 The ny+1 valence linking group represented by the symbol is preferably a ny+1 valence hydrocarbon group with 1 to 15 carbon atoms that can have substituents other than fluorine atoms, and a portion of the carbon atoms constituting the hydrocarbon group can be replaced by heteroatoms. For example, in the -CH2- constituting part of the ny+1 valence hydrocarbon group, one or more non-adjacent -CH2- atoms can be independently replaced by -O-, -CO-, -S-, or -N(Q)-. In addition, Q represents a hydrogen atom or a substituent. As the substituent represented by Q, it is preferably an alkyl group, more preferably a straight-chain alkyl group with 1 to 4 carbon atoms, and even more preferably methyl or ethyl. Furthermore, >C< (carbon atom) can be replaced by >Si< (silicon atom).

[0118] ny represents an integer greater than 2. ny is preferably an integer from 2 to 8, more preferably an integer from 3 to 6, and even more preferably an integer from 3 to 5.

[0119] The content of repeating units having groups represented by formula (2) is preferably 25 to 65% by mass relative to all repeating units contained in the polymer.

[0120] The polymer described above preferably contains repeating units having polymerizable groups.

[0121] As described above, it is a polymerizable group.

[0122] As a repeating unit with polymerizable groups, the repeating unit represented by formula (Z) can be cited as an example.

[0123] [Chemical Formula 4] R z1 and R z2 Each can be used to represent a hydrogen atom or an alkyl group independently.

[0124] The number of carbon atoms in alkyl groups is not particularly limited, but is preferably 1 to 18.

[0125] Alkyl groups can be any of the following structures: straight-chain, branched, or cyclic.

[0126] R z3 It represents a hydrogen atom or a substituent.

[0127] Examples of substituents include hydroxyl, alkyl, alkenyl, and aryl.

[0128] L z It indicates a divalent linker.

[0129] The divalent linking group is not particularly limited, and examples include alkylene (preferably alkylene with 1 to 20 carbon atoms), arylene, -O-, -S-, -CO-, -SO-, -SO2-, and -NR. a - Or a divalent linking group formed by combining multiple of them. R a It represents a hydrogen atom or an alkyl group.

[0130] R z4 It indicates a polymerizable group.

[0131] The content of repeating units having polymerizable groups is preferably 5 to 40 by mass relative to all repeating units contained in the polymer.

[0132] The weight-average molecular weight of polymers having groups represented by formula (1) is preferably 5,000 to 200,000.

[0133] The content of the polymerizable liquid crystal compound in the composition is not particularly limited, but is preferably 50 to 99.9% by mass, more preferably 80 to 99% by mass, relative to the total solid content in the composition.

[0134] The content of the above-mentioned polymer in the composition is not particularly limited, but is preferably 0.001 to 5.0% by mass, more preferably 0.01 to 2.0% by mass, relative to the total solid content in the composition.

[0135] Solid components refer to components in a composition other than the solvent. Furthermore, even if a component is in liquid form, it is considered a solid component.

[0136] <Positive C Board> The definition of a positive C-plate is as described above.

[0137] The thickness direction delay of the positive C plate at a wavelength of 550 nm, i.e., Rth (550), is not particularly limited, but from the viewpoint that the polarizer of the present invention is more superior as a circular polarizer, it is preferably -120 to -10 nm, and more preferably -100 to -30 nm.

[0138] The structure of the positive C-plate is not particularly limited; examples include a vertically oriented liquid crystal layer (a layer formed by fixing vertically oriented rod-shaped liquid crystal compounds) and a polymer film. From the viewpoint of achieving better results in this invention, a laminate of the vertically oriented liquid crystal layer and the polymer film is preferred. That is, the positive C-plate preferably includes a vertically oriented liquid crystal layer and a polymer film.

[0139] Furthermore, when the positive C-plate comprises a vertically aligned liquid crystal layer and a polymer film, an optically isotropic layer (e.g., an adhesive layer) may be further included between the vertically aligned liquid crystal layer and the polymer film. An optically isotropic layer is defined as a layer with an in-plane retardation Re of 10 nm or less at a wavelength of 550 nm and an absolute value of a thickness-direction retardation Rth of 10 nm or less at a wavelength of 550 nm. As described above, when the positive C-plate includes an optically isotropic layer between the vertically aligned liquid crystal layer and the polymer film, the thickness of the optically isotropic layer is also included in the thickness of the positive C-plate. Furthermore, from the viewpoint of superior adhesion between the vertically aligned liquid crystal layer and the polymer film, direct contact between the vertically aligned liquid crystal layer and the polymer film is preferred.

[0140] Furthermore, the vertical orientation of the rod-shaped liquid crystal compound means that the long axis of the rod-shaped liquid crystal compound is parallel to the thickness direction of the positive C-plate. However, strict parallelism is not required; the angle between the long axis of the rod-shaped liquid crystal compound and the thickness direction of the first positive C-plate is preferably within the range of 0 ± 20°, and more preferably within the range of 0 ± 10°.

[0141] Furthermore, the vertically oriented liquid crystal layer is preferably formed by polymerizing a polymeric rod-shaped liquid crystal compound that is fixed in a vertical orientation.

[0142] When the vertically oriented liquid crystal layer of the positive C-plate is in direct contact with the polymer film, the polymer film preferably includes a region (designated as region A) containing components derived from the liquid crystal compound contained in the vertically oriented liquid crystal layer. From the viewpoint of adhesion and the orientation of the vertically oriented liquid crystal layer, the thickness of region A is preferably 20 to 200 nm. Region A preferably contains a vertically oriented liquid crystal compound.

[0143] Methods for controlling the thickness of region A include adjusting the type of solvent or the concentration of solid components contained in the composition for forming the vertically aligned liquid crystal layer, including the inclusion of a crosslinking polymer or vertical alignment agent in the vertically aligned liquid crystal layer, and controlling the thickness of region A by adjusting the drying or heating conditions of the vertically aligned liquid crystal layer.

[0144] Whether a polymer film contains a region A containing components derived from liquid crystal compounds contained in a vertically oriented liquid crystal layer can be confirmed by performing time-of-flight secondary ion mass spectrometry while irradiating the polymer film side of the vertically oriented liquid crystal layer with an ion beam, and measuring the secondary ion intensity of the components derived from the liquid crystal compound in the vertically oriented liquid crystal layer, whether the secondary ion intensity I of the components derived from the liquid crystal compound in the polymer film satisfies the following formula (I-1), and whether there is a thickness of the region of the polymer film containing the surface of the vertically oriented liquid crystal layer.

[0145] In the formula, Ic represents the average value of the secondary ion intensity of the liquid crystal compound component originating from the vertically aligned liquid crystal layer in the central region from the surface of the polymer film side of the vertically aligned liquid crystal layer, at a depth position corresponding to 40% of the overall thickness of the vertically aligned liquid crystal layer to a depth position corresponding to 60%.

[0146] 0.05≤I / Ic (I-1) As a rod-shaped liquid crystal compound, known compounds can be used.

[0147] Examples of rod-shaped liquid crystal compounds include those exemplified in the positive A plate.

[0148] Liquid crystal compounds (preferably rod-shaped liquid crystal compounds) may have polymerizable groups.

[0149] The types of polymerizable groups that liquid crystal compounds can have are as described above.

[0150] The thickness of the positive C plate is 20.0 to 70.0 μm, and from the viewpoint of further suppressing the occurrence of curling, it is preferably 25.0 to 60.0 μm, and more preferably 30.0 to 50.0 μm.

[0151] Furthermore, the thickness of the positive C-plate refers to its average thickness. This average thickness is calculated by measuring the thickness at any five or more points on the positive C-plate and taking their arithmetic mean. The thickness can be measured, for example, using a reflective spectrophotometer FE3000.

[0152] As one of the preferred methods for the positive C-plate, it is preferable to include a polymer film, and more preferably, it includes a vertically aligned liquid crystal layer and a polymer film.

[0153] The resin constituting the polymer film is not particularly limited, and known resins can be cited. More specifically, examples of such resins include cellulose-based resins (hereinafter also referred to as cellulose acylates), represented by triacetylcellulose; norbornene-based resins (such as ZEONEX and ZEONOR manufactured by Zeon Corporation, and ARTON manufactured by JSR Corporation); acrylic resins; polyester resins; and polystyrene-based resins. Among these, a film containing a cellulose-based resin is preferred as the polymer film, and a cellulose acylate film is more preferred.

[0154] The thickness direction delay of the polymer film at a wavelength of 550 nm is not particularly limited. From the viewpoint that the polarizer of the present invention is more superior as a circular polarizer, it is preferably -120 to 30 nm, and more preferably -100 to 30 nm.

[0155] The in-plane retardation of the polymer film at a wavelength of 550 nm is not particularly limited, but from the viewpoint that the polarizer of the present invention is superior as a circular polarizer, it is preferably 10 nm or less. The lower limit is not particularly limited and is 0 nm.

[0156] The thickness of the polymer film is not particularly limited, but from the viewpoint of further suppressing curling, it is preferably 15.0 to 65.0 μm, more preferably 25.0 to 60.0 μm, and especially preferably 30.0 to 50.0 μm.

[0157] Furthermore, the thickness of the polymer film refers to its average thickness. This average thickness is calculated by measuring the thickness of any five or more points on the polymer film and then taking their arithmetic average.

[0158] As described above, the vertically oriented liquid crystal layer is a layer formed by fixing vertically oriented rod-shaped liquid crystal compounds.

[0159] When the positive C-plate includes a vertically oriented liquid crystal layer and a polymer film, from the viewpoint of better adhesion between the vertically oriented liquid crystal layer and the polymer film, the vertically oriented liquid crystal layer preferably includes a crosslinker that is biased towards the polymer film side. As a crosslinker, examples include crosslinkers formed by crosslinking polymers having crosslinking groups, which will be described later.

[0160] Examples of crosslinking groups include the polymeric groups mentioned above.

[0161] In addition, the fact that crosslinks are more prevalent on the polymer film side means that when the vertically oriented liquid crystal layer is divided into two parts along the thickness direction, the crosslink content in the divided region on the polymer film side is greater than the crosslink content in the divided region on the opposite side of the polymer film side.

[0162] One preferred method for vertically oriented liquid crystal layers is to use a layer formed by a composition comprising a liquid crystal compound and a crosslinked polymer, wherein the crosslinked polymer has hydroxyl groups. Because the crosslinked polymer has hydroxyl groups, polymers with crosslinked groups tend to be present on the polymer film side (especially cellulose acylate films). As a result, as described above, crosslinked products formed by crosslinking a crosslinked polymer tend to be present on the polymer film side.

[0163] Examples of liquid crystal compounds contained in the composition include the liquid crystal compounds described above.

[0164] The crosslinkable polymer preferably contains repeating units having crosslinking groups.

[0165] As described above, polymerizable groups are preferred as crosslinking groups. That is, the crosslinking polymer preferably contains repeating units having polymerizable groups.

[0166] As a repeating unit with polymerizable groups, the repeating unit represented by formula (Z) above can be cited as an example.

[0167] From the viewpoint of favoring the presence of crosslinks on the polymer film side, the crosslinked polymer preferably does not have any of the following: fluorine atoms, silicon atoms, and photo-orientation groups (e.g., cinnamyl or azo groups). That is, the crosslinked product formed by crosslinking the crosslinked polymer preferably does not have any of the following: fluorine atoms, silicon atoms, and photo-orientation groups.

[0168] The content of repeating units having cross-linking groups is preferably 50 to 99% by mass relative to all repeating units contained in the cross-linked polymer.

[0169] Crosslinkable polymers preferably contain repeating units having hydroxyl groups.

[0170] The number of hydroxyl groups contained in the repeating unit is not particularly limited, preferably 1 to 3, more preferably 1 or 2.

[0171] The content of repeating units with hydroxyl groups is preferably 1 to 30% by mass relative to all repeating units contained in the crosslinked polymer.

[0172] The crosslinked polymer may have repeating units different from the repeating units described above. The content of the different repeating units is preferably 1 to 30% by mass relative to all repeating units contained in the crosslinked polymer.

[0173] The weight-average molecular weight of the crosslinked polymer is preferably 5,000 to 200,000.

[0174] Specific examples of crosslinked polymers include, for example, the following structures, but are not limited thereto. The a to c described in the repeating units represent the content (mass %) of each repeating unit relative to all repeating units.

[0175] [Chemical Formula 5] The content of liquid crystal compound in the composition is not particularly limited, but is preferably 50 to 99% by mass, more preferably 80 to 95% by mass, relative to the total solid content in the composition.

[0176] The content of the above-mentioned crosslinked polymer in the composition is not particularly limited, but is preferably 0.1 to 20% by mass, more preferably 1 to 5% by mass, relative to the total solid content in the composition.

[0177] Solid components refer to components in a composition other than the solvent. Furthermore, even if a component is in liquid form, it is considered a solid component.

[0178] The vertically aligned liquid crystal layer preferably contains an alignment control agent. The alignment control agent can be any alignment control agent that functions to vertically align the liquid crystal, and known materials can be selected.

[0179] When the composition for forming a vertically oriented liquid crystal layer contains the aforementioned crosslinked polymer containing hydroxyl groups, from the viewpoint of achieving higher orientation, it is preferable to use an onium salt compound as an orientation control agent.

[0180] The vertically oriented liquid crystal layer preferably contains a photoisomerizing compound on its surface opposite to the polymer film side. As described later, by including a photoisomerizing compound in the vertically oriented liquid crystal layer, a positive A-plate can be directly formed on the vertically oriented liquid crystal layer, thereby improving the adhesion between the vertically oriented liquid crystal layer and the positive A-plate.

[0181] There are no particular limitations on photoisomerizing compounds, as long as they are capable of photoisomerization; examples include compounds with photoisomerizing groups. Examples of photoisomerizing groups include cinnamyl, chalcone, azophenyl, and stilbene.

[0182] The photoisomerizing compound preferably contains repeating units having photoisomerizing groups.

[0183] The content of repeating units having photoisomerizing groups is preferably 5 to 45% by mass relative to all repeating units contained in the photoisomerizing compound.

[0184] The photoisomerization compound preferably contains repeating units having groups represented by formula (2).

[0185] The content of repeating units having groups represented by formula (2) is preferably 20 to 60% by mass relative to all repeating units contained in the photoisomerized compound.

[0186] The thickness of the vertically aligned liquid crystal layer is not particularly limited, but from the viewpoint of further suppressing the occurrence of curling, it is preferably 10 μm or less, and more preferably 0.1 to 5.0 μm.

[0187] Furthermore, the thickness of the vertically aligned liquid crystal layer refers to the average thickness of the vertically aligned liquid crystal layer. This average thickness is calculated by measuring the thickness at any five or more points on the vertically aligned liquid crystal layer and then averaging them. The thickness measurement can be performed, for example, using a reflective spectrophotometer FE3000.

[0188] When the vertically aligned liquid crystal layer is in direct contact with the positive A plate, from the viewpoint of adhesion, it is preferable that the vertically aligned liquid crystal layer includes a region (designated as region B) containing components derived from the liquid crystal compound contained in the positive A plate. The thickness of region B is preferably 5 to 100 nm.

[0189] The methods used to determine region B are the same as those used for region A.

[0190] <Adhesive layer> The adhesive layer is a layer formed using an adhesive.

[0191] Examples of adhesives include rubber-based adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl alcohol adhesives, polyvinylpyrrolidone adhesives, polyacrylamide adhesives, and cellulose adhesives, with acrylic adhesives or polyvinyl alcohol adhesives (PVA adhesives) being preferred.

[0192] As an acrylic adhesive, a copolymer of (meth)acrylates with alkyl groups of 20 or fewer carbon atoms, such as methyl, ethyl or butyl, in the ester portion, and (meth)acrylate monomers having functional groups such as (meth)acrylate or (meth)acrylate hydroxyethyl ester is preferred.

[0193] The thickness of the adhesive layer is not particularly limited, but as a lower limit, it is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 15 μm or more. As an upper limit, it is preferably 45 μm or less, more preferably 30 μm or less, and even more preferably 25 μm or less.

[0194] <Other Layers> The polarizer with adhesive layer of the present invention may include other components besides those described above.

[0195] For example, to improve the fit between components, the polarizer with adhesive layer of the present invention may further have an adhesive layer.

[0196] The adhesive layer is selected from the group consisting of the adhesive layer and the bonding agent layer.

[0197] An adhesive layer is a layer formed by using an adhesive. For example, a layer formed by curing an adhesive can be cited.

[0198] Examples of adhesives include, for example, active energy radiation-curable adhesives and thermosetting adhesives. Examples of active energy radiation-curable adhesives include electron beam-curable adhesives, ultraviolet-curable adhesives, and visible light-curable adhesives, with ultraviolet-curable adhesives being preferred. That is, the adhesive layer is preferably a layer formed by curing an ultraviolet-curable adhesive.

[0199] Specific examples of active energy ray-curable adhesives include (meth)acrylate adhesives. Among the curing components of (meth)acrylate adhesives are compounds having (meth)acryloyl groups and compounds having vinyl groups.

[0200] Polyvinyl alcohol-based adhesives (PVA adhesives) are also preferred as adhesives.

[0201] Examples of polyvinyl alcohol-based adhesives include adhesives composed of polyvinyl alcohol or its derivatives. Examples of polyvinyl alcohol derivatives include polyvinyl formal and polyvinyl acetal. In addition, examples include olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid and crotonic acid and their alkyl esters, or substances modified with acrylamide.

[0202] The thickness of the adhesive layer is not particularly limited, but as a lower limit, it is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.5 μm or more. As an upper limit, it is preferably 5 μm or less, more preferably 2 μm or less.

[0203] As an adhesive layer, an example can be given as the adhesive layer contained in the aforementioned polarizer with an adhesive layer.

[0204] Preferably, the polarizer and the positive A plate are laminated together via an adhesive layer, and more preferably via a polyvinyl alcohol-based adhesive layer.

[0205] Furthermore, it is preferable that the polarizer and the positive A plate are laminated together via an adhesive layer, which is formed by curing an ultraviolet-curable adhesive.

[0206] Furthermore, the polarizer with adhesive layer of the present invention can also have a cover film on the protective film for protecting the protective film. By having a cover film, scratches on the protective film during operation can be further prevented.

[0207] When the polarizer with adhesive layer of the present invention is bonded to a glass substrate by adhesive, and a cross-cut test of 100 grids is performed on the bonded polarizer with adhesive layer, the number of grids peeled off is preferably 50 or less.

[0208] In this invention, a polymer film is sometimes included as part of the positive C-plate. However, the polymer film adheres well to adjacent layers when laminated, and therefore is not easily peeled off in the cross-cut test described above. That is, in the cross-cut test described above, peeling is not easily generated between the polymer film and the layers adjacent to the polymer film.

[0209] The above cross-cut test can be performed according to JIS-K5600-5-6 (1999).

[0210] <Method for manufacturing polarizers with adhesive layer> The method for manufacturing the polarizer with adhesive layer of the present invention is not particularly limited and can be manufactured by known methods.

[0211] For example, a polarizer with an adhesive layer can be manufactured by fabricating various components that constitute a polarizer with an adhesive layer and then stacking these components via the aforementioned adhesive layer, or by directly stacking the components without an adhesive layer. More specifically, a polarizer can be manufactured by conveying a polarizer while attaching a protective film to one surface of the polarizer and attaching a laminated film containing a positive A plate and a positive C plate to the other surface of the polarizer, and then depositing an adhesive layer on the positive C plate side of the resulting polarizer.

[0212] The positive A-plate is preferably formed using a composition containing a polymerizable liquid crystal compound. More specifically, it is preferable to coat the composition containing the polymerizable liquid crystal compound, perform an orientation treatment on the formed coating to orient the polymerizable liquid crystal compound in the coating, and then perform a curing treatment to manufacture the positive A-plate.

[0213] Examples of components contained in the above-described compositions include the polymeric liquid crystal compound and polymers having groups represented by formula (1).

[0214] Other components that may be included in the above composition, in addition to those mentioned above, include monomers, polymerization initiators, photoacid generators, orientation control agents (vertical orientation agents, horizontal orientation agents), surfactants, adhesion improvers, plasticizers, and solvents.

[0215] Examples of substrates having an alignment film can be used as coating compositions. The alignment film can be a photoalignment film.

[0216] Examples of coating methods for the composition include curtain coating, dip coating, spin coating, printing coating, spray coating, slot coating, roller coating, sliding coating, doctor blade coating, gravure coating, and wire rod coating.

[0217] Orientation processing can be performed by drying the coating at room temperature or by heating the coating. In the case of thermotropic liquid crystal compounds, the liquid crystal phase formed by orientation processing can typically change according to changes in temperature or pressure. In the case of lyotropic liquid crystal compounds, the phase can also change according to the composition ratio of solvents, etc.

[0218] In addition, the conditions for heating the coating are not particularly limited, but the heating temperature is preferably 50 to 250°C, more preferably 50 to 150°C, and the heating time is preferably 10 seconds to 10 minutes.

[0219] Furthermore, after heating the coating, it can be cooled as needed before the curing process (light irradiation treatment) described later.

[0220] The method for curing the coating film on which the polymeric liquid crystal compound is oriented is not particularly limited; examples include light irradiation and heat treatment. From the viewpoint of manufacturing suitability, light irradiation is preferred, and ultraviolet irradiation is more preferred.

[0221] The irradiation conditions for light treatment are not particularly limited, but are preferably 50–1000 mJ / cm². 2 The amount of radiation.

[0222] The atmosphere during light irradiation is not particularly restricted, but a nitrogen atmosphere is preferred.

[0223] As a method for manufacturing the positive C plate, similar to the method for manufacturing the positive A plate described above, a method using a composition containing a polymerizable liquid crystal compound can be cited.

[0224] The composition may contain polymerizable liquid crystal compounds, crosslinked polymers, and photoisomerizing compounds. When a photoisomerizing compound is included in the composition, the photoisomerizing compound may have polymerizable groups.

[0225] In addition, when the positive C plate includes a vertically aligned liquid crystal layer and a polymer film, the above composition can be coated onto the polymer film to form a vertically aligned liquid crystal layer.

[0226] Furthermore, in this invention, a composition for forming a positive A plate can be coated onto a positive C plate, thereby forming a positive A plate directly laminated onto the positive C plate.

[0227] In the above-described steps, a photoisomerizing compound can be disposed on the surface side of the positive C-plate on the side forming the positive A-plate, and the photoisomerizing compound can be irradiated with light to impart the function of a photoalignment film. For example, when the positive C-plate comprises a vertically aligned liquid crystal layer and a polymer film, and the positive A-plate is formed by coating a composition on the vertically aligned liquid crystal layer, a photoisomerizing compound can be disposed on the surface of the vertically aligned liquid crystal layer opposite to the polymer film side, and irradiated with light to orient the photoisomerizing groups contained in the photoisomerizing compound, thereby imparting alignment capability to the surface of the vertically aligned liquid crystal layer.

[0228] <Uses> The polarizer with adhesive layer of the present invention can be preferably applied to display devices. More specifically, the polarizer with adhesive layer of the present invention having the above-described structure is preferably used for anti-reflective applications in display devices such as liquid crystal display (LCD), plasma display panel (PDP), electroluminescent display (ELD), and cathode ray tube display (CRT).

[0229] The display device of the present invention includes a display element and the polarizer with an adhesive layer described above.

[0230] When applying the polarizer with adhesive layer of the present invention to a display device, a method can be described as attaching the display element and the polarizer with adhesive layer by setting the adhesive layer in the polarizer with adhesive layer on the display element side.

[0231] Display elements are not particularly limited; examples include organic electroluminescent display elements and liquid crystal display elements.

[0232] Example The following examples and comparative examples further illustrate the features of the present invention. The materials, amounts, proportions, processing contents, and processing steps shown in the following examples can be appropriately modified without departing from the spirit of the present invention. Therefore, the scope of the present invention is not to be limited by the specific examples shown below.

[0233] <Example 1> (Preparation of cellulose acylated film (1)) The following composition was added to a mixing vessel and stirred, then heated at 90°C for 10 minutes. The resulting composition was then filtered through filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm to prepare a paste. The solids concentration of the paste was 23.5% by mass, and the solvent was dichloromethane / methanol / butanol in a mass ratio of 81 / 18 / 1.

[0234] ―――――――――――――――――――――――――――――――― Cellulose acylated gel ―――――――――――――――――――――――――――――――― Cellulose acylated compound (acetyl substitution degree 2.86, viscosity-uniform polymerization degree 310) 100 parts by weight Sugar ester compound 1 (shown by formula (S4) below) 6.0 parts by mass Sugar ester compound 2 (shown by formula (S5) below) 2.0 parts by mass 0.1 parts by weight of silica particle dispersion (AEROSIL R972, manufactured by NIPPON AEROSIL CO.,LTD.) Solvents (dichloromethane / methanol / butanol) ―――――――――――――――――――――――――――――――― [Chemical Formula 6] [Chemical Formula 7] The adhesive paste prepared above was cast using a roller film casting machine. The adhesive paste was cast from the die head to contact a metal support cooled to 0°C, and then the resulting web (film) was peeled off. The roller was made of SUS.

[0235] After peeling the web (film) obtained by casting from the rollers, the web was dried for 20 minutes in a stretching device at 30–40°C using clamps that held both ends of the web. Then, the web was post-dried by zone heating while being conveyed by rollers. After knurling the obtained web, it was wound up to produce a cellulose acylated film with a thickness of 40 μm (1).

[0236] The cellulose acylated membrane (1) has an in-plane retardation of 0 nm at a wavelength of 550 nm and a thickness retardation of 23 nm at a wavelength of 550 nm.

[0237] (Formation of the positive C plate (1A)) Using a casting coater, a vertically aligned liquid crystal layer forming composition (1A) comprising a rod-shaped liquid crystal compound with the following composition was coated onto the above-mentioned cellulose acylate film to form a composition layer. The film with the composition layer formed was heated at 60°C for 1 minute with warm air, and simultaneously purged with nitrogen to achieve an oxygen concentration of less than 100 ppm by volume, and irradiated with a 365 nm UV-LED at an irradiation dose of 100 mJ / cm². 2The ultraviolet light was then used to anneal the obtained coating at 130°C for 1 minute with warm air, thereby forming a positive C plate (1A) with a thickness of 40.7 μm on which a vertically aligned liquid crystal layer (1A) with a thickness of 0.7 μm was formed on the cellulose acylate film.

[0238] Furthermore, the positive C plate (1A) exhibits an in-plane retardation Re of 0 nm at a wavelength of 550 nm and a thickness-direction retardation Rth of -85 nm at a wavelength of 550 nm. It was confirmed that the long axis of the rod-shaped liquid crystal compound has an average tilt angle of 90° relative to the film surface and is perpendicularly oriented relative to the film surface.

[0239] ―――――――――――――――――――――――――――――――― Composition for forming a vertically aligned liquid crystal layer (1A) ―――――――――――――――――――――――――――――――― 100 parts by weight of the following rod-shaped liquid crystal compound (A) Polymerizable monomer (A-400, manufactured by SHIN-NAKAMURA CHEMICAL CO, LTD.) 4.2 parts by weight The following polymerization initiator S-1 (oxime type) is present in 5.1 parts by weight. The following photoacid-generating agent D-1, 3.0 parts by weight The following polymer M-1 4.0 parts by weight The following orientation control agent A-1, 1.9 parts by weight The following photo-oriented polymer PA-1, 0.8 parts by weight 0.2 parts by weight of diisopropylethylamine 93.8 parts by weight of methyl ethyl ketone 372.0 parts by weight of methyl isobutyl ketone ―――――――――――――――――――――――――――――――― Rod-shaped liquid crystal compound (A) (The following numerical values ​​for mixtures of compounds represent mass ratios.) [Chemical Formula 8] Polymerization initiator S-1 [Chemical Formula 9] Photoacid generator D-1 [Chemical Formula 10] Polymer M-1 (weight-average molecular weight 52,000. Values ​​listed in repeating units indicate the content (mass%) of each repeating unit relative to all repeating units.) [Chemical Formula 11] Orientation control agent A-1 [Chemical Formula 12] Photooriented polymer PA-1 (The values ​​listed in the repeating units indicate the content (mass%) of each repeating unit relative to all repeating units. Weight-average molecular weight: 90,000. Me indicates methyl.) [Chemical Formula 13] (Making of the A-plate (1B)) UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYA) passing through a wire grid polarizer was shone onto the vertically aligned liquid crystal layer (1A) side of the elongated positive C-plate (1A). The light concentration was 7.9 mJ / cm². 2 (Wavelength: 313nm), thereby forming a composition layer with orientation control capability on the surface. Next, using a casting coater, a horizontally aligned liquid crystal layer forming composition (1B) containing a rod-shaped liquid crystal compound of the following composition is coated onto the vertically aligned liquid crystal layer (1A). After temporarily heating to 120°C with warm air, it is cooled to 60°C to stabilize the orientation. Then, the film temperature is maintained at 60°C under a nitrogen atmosphere (oxygen concentration less than 100ppm) using an ultra-high pressure mercury lamp for the first ultraviolet irradiation (80mJ / cm²). 2 After that, the film temperature was maintained at 100℃ and subjected to a second ultraviolet irradiation (300mJ / cm). 2 This fixes the orientation, thus forming the positive A plate (1B).

[0240] The thickness of the positive A plate (1B) is 2.8 μm, and the Re (550) at a wavelength of 550 nm is 141 nm. If the width direction of the film is set to 0° (and the length direction is set to 90°), then the in-plane slow axis direction (the orientation axis angle of the liquid crystal compound) is 45°.

[0241] ―――――――――――――――――――――――――――――――― Composition for forming a horizontally aligned liquid crystal layer (1B) ―――――――――――――――――――――――――――――――― The following rod-shaped liquid crystal compound (B) in 21.2 parts by weight The following rod-shaped liquid crystal compound (C) is present in 26.1 parts by weight. The following rod-shaped liquid crystal compound (D) 29.0 parts by mass The following rod-shaped liquid crystal compound (E) 8.5 parts by weight The following rod-shaped liquid crystal compound (F) 15.3 parts by weight The above polymerization initiator S-1 (oxime type) 0.5 parts by weight The following leveling agent L-1, 0.1 parts by weight Cyclopentanone 175.0 parts by weight 50.0 parts by weight of methyl ethyl ketone 10.0 parts by weight of ethyl laurate ―――――――――――――――――――――――――――――――― Rod-shaped liquid crystal compound (B) [Chemical Formula 14] Rod-shaped liquid crystal compound (C) [Chemical Formula 15] Rod-shaped liquid crystal compounds (D) [Chemical Formula 16] Rod-shaped liquid crystal compounds (E) [Chemical Formula 17] Rod-shaped liquid crystal compounds (F) [Chemical Formula 18] Leveling agent L-1 (weight average molecular weight 28,500. The values ​​listed in the repeating units indicate the content (mass%) of each repeating unit relative to all repeating units.) [Chemical Formula 19] Through the above steps, a long strip-shaped laminated film (1) with a thickness of 43.5 μm was fabricated by directly stacking positive C plate (1A) and positive A plate (1B).

[0242] (Preparation of PVA adhesive) The PVA adhesive was prepared as follows: 100 parts by mass of polyvinyl alcohol resin with acetylacetyl groups (average degree of polymerization: 1200, degree of saponification: 98.5 mol%, degree of acetylacetylation: 5 mol%) and 20 parts by mass of hydroxymethyl melamine were dissolved in pure water at a temperature of 30°C, and the concentration of solid components was adjusted to 3.7 mol / L.

[0243] (Preparation of the adhesive layer) An adhesive layer (acrylic adhesive) with a thickness of 20 μm was formed on the diaphragm using the same method as described in Example 1 of Japanese Patent Application Publication No. 2023-126297.

[0244] (Fabrication of polarizer (P1)) The surface of the support for the cellulose triacetate film TJ25 (manufactured by FUJIFILM Corporation: 25 μm thickness) was subjected to alkaline saponification treatment. Specifically, the support was immersed in a 1.5 equivalent sodium hydroxide aqueous solution at 55°C for 2 minutes, then cleaned in a water bath at room temperature, and further neutralized with 0.1 equivalent sulfuric acid at 30°C. After neutralization, the support was cleaned in a water bath at room temperature and further dried with warm air at 100°C, thereby obtaining the polarizer protective film (1).

[0245] A 60 μm thick roll of polyvinyl alcohol (PVA) film was continuously stretched and dried along its length in an iodine aqueous solution to obtain a polarizer (1) with a thickness of 13 μm. The transmittance of the polarizer (1) was 43% for the visibility correction monomer. At this time, the absorption axis of the polarizer (1) was aligned with the length direction.

[0246] On one side of the polarizer (1), the positive A plate (1B) of the elongated laminated film (1) prepared above was bonded to the surface using the above-mentioned PVA adhesive. On the other side of the polarizer (1), the polarizer protective film (1) was bonded to the surface using the above-mentioned PVA adhesive. Then, a laminated film made of PET (polyethylene terephthalate) film with a weak adhesive and a thickness of 50 μm was bonded to the side of the polarizer protective film (1). Then, an adhesive layer formed on the above-mentioned diaphragm was bonded to the side of the laminated film (1). Through the above steps, a polarizer (P1) with an adhesive layer was produced.

[0247] At this time, the following are stacked in sequence: laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), PVA adhesive layer (thickness 0.2μm), positive A plate (1B), positive C plate (1A) (vertically aligned liquid crystal layer (1A), cellulose acylate film (1)), adhesive layer and diaphragm. The angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (1B) is 45°.

[0248] <Example 2> A cellulose acylated film (2) with a thickness of 20 μm was prepared using the same method as the cellulose acylated film (1) described above. The cellulose acylated film (1) was replaced with the cellulose acylated film (2). Otherwise, a laminated film (2) with a thickness of 23.5 μm, consisting of a positive C plate (2A) and a positive A plate (2B), and a polarizer (P2) with an adhesive layer were prepared using the same method as in Example 1.

[0249] <Comparative Example 1> A cellulose acylated film (3) with a thickness of 15 μm was prepared using the same method as the cellulose acylated film (1) described above. The cellulose acylated film (1) was replaced with the cellulose acylated film (3). Otherwise, a laminated film (3) with a thickness of 18.5 μm, consisting of a positive C plate (3A) and a positive A plate (3B), and a polarizer (P3) with an adhesive layer were prepared using the same method as in Example 1.

[0250] <Example 3> On one side of the polarizer (1) produced in the method of Example 1, the polarizer protective film (1) is bonded with the above-mentioned PVA adhesive to form a single-sided polarizer (1). Furthermore, a laminated film consisting of a PET film with a weak adhesive and a thickness of 50 μm is bonded to the side of the polarizer protective film (1).

[0251] After corona treatment of the surface of the laminated film (1) prepared in Example 1 on the positive A plate (1B) side and the surface of the polarizer side of the single-sided polarizer (1) prepared above, the two films are bonded together using the ultraviolet-curable adhesive composition (1) with the following composition, so that the length directions of the two films are parallel, and ultraviolet light (600 mJ / cm) is irradiated from the laminated film (1) side. 2 After curing, an adhesive layer formed on the diaphragm is then bonded to it, thereby producing a polarizer with an adhesive layer (P4).

[0252] ―――――――――――――――――――――――――――――――― UV-curable adhesive composition (1) ―――――――――――――――――――――――――――――――― CEL2021P (manufactured by Daicel Corporation) 70.0 parts by weight 10.0 parts by weight of 2-ethylhexyl glycidyl ether RIKARESIN DME-100 (manufactured by New Japan Chemical Co., Ltd.) 20.0 parts by weight CPI-100P (manufactured by San-Apro Ltd.) 4.5 parts by weight ―――――――――――――――――――――――――――――――― At this time, the laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), adhesive layer (adhesive layer made by curing UV-curable adhesive composition, thickness 1μm), positive A plate (1B), positive C plate (1A), adhesive layer and diaphragm are stacked in sequence, and the angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (1B) is 45°.

[0253] <Example 4> By changing polymer M-1 used in the vertically aligned liquid crystal layer forming composition (1A) to polymer M-2 described below, a vertically aligned liquid crystal layer forming composition (5A) was produced.

[0254] Polymer M-2 (weight-average molecular weight 60,000. Values ​​listed in repeating units indicate the content (mass%) of each repeating unit relative to all repeating units.) [Chemical Formula 20] By changing the vertically aligned liquid crystal layer forming composition (1A) to the vertically aligned liquid crystal layer forming composition (5A), a positive C-plate (5B) formed from the vertically aligned liquid crystal layer (5A) and the cellulose acylate film (1) was fabricated using the method described in Example 1. Next, a positive A-plate (5B) was formed on the surface of the vertically aligned liquid crystal layer (5A) using the same method as the positive A-plate (1B), thereby fabricating a strip-shaped laminated film (5) with a thickness of 40.7 μm in which the positive C-plate (5A) and the positive A-plate (5B) are directly stacked.

[0255] On the polarizer (1) side of the aforementioned single-sided polarizer (1), the positive A plate (5B) side of the laminated film (5) is bonded with the aforementioned UV-curable adhesive composition (1), and ultraviolet light (600 mJ / cm²) is irradiated from the laminated film (5) side. 2 After curing, an adhesive layer formed on the diaphragm is further bonded together, thereby producing a polarizer with an adhesive layer (P5).

[0256] At this time, the polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), adhesive layer (adhesive layer made by curing UV-curable adhesive composition, thickness 1μm), positive A plate (5B), vertically aligned liquid crystal layer (5A), cellulose acylate film (1), adhesive layer and diaphragm are stacked in sequence, and the angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (5B) is 45°.

[0257] <Comparative Example 2> In the method described in Example 4, after the laminated film (5) is bonded to the polarizer (1), the cellulose acylated film (1) is peeled off, and then an adhesive layer formed on the diaphragm is bonded, thereby producing a polarizer (P6) with an adhesive layer sequentially laminated with a laminated film, a polarizer protective film (1), a PVA adhesive layer (0.2 μm thick), a polarizer (1), an adhesive layer (an adhesive layer made of a UV-curable adhesive composition, 1 μm thick), a positive A plate (5B), a positive C plate (6A) formed from a vertically aligned liquid crystal layer (5A), an adhesive layer, and a diaphragm.

[0258] <Example 5> (Making of the C-plate (7A)) Using a casting coating machine, a vertically aligned liquid crystal layer forming composition (7A) comprising a rod-shaped liquid crystal compound with the following composition was coated onto the above-mentioned cellulose acylated film (1) to form a composition layer. The film with the composition layer formed was heated at 60°C for 1 minute with warm air, and while being purged with nitrogen to achieve an oxygen concentration of less than 100 ppm by volume, it was irradiated with a 365 nm UV-LED with an irradiation dose of 100 mJ / cm². 2 The ultraviolet light was then used to anneal the obtained coating at 130°C for 1 minute with warm air to form a positive C-plate (7A) with a thickness of 40.7 μm, consisting of a vertically aligned liquid crystal layer (7A) with a thickness of 0.7 μm and a cellulose acylate film (1). The positive C-plate (7A) had an in-plane retardation Re of 0 nm at a wavelength of 550 nm and a thickness direction retardation Rth of -85 nm at a wavelength of 550 nm. It was confirmed that the long axis of the rod-shaped liquid crystal compound had an average tilt angle of 90° relative to the film surface and was vertically aligned relative to the film surface.

[0259] ―――――――――――――――――――――――――――――――― Composition for forming a vertically aligned liquid crystal layer (7A) ―――――――――――――――――――――――――――――――― 100 parts by mass of the above-mentioned rod-shaped liquid crystal compound (A) Polymerizable monomer (A-400, manufactured by SHIN-NAKAMURA CHEMICAL CO, LTD.) 4.2 parts by weight The above-mentioned polymerization initiator S-1 (oxime type) 5.1 parts by weight The above-mentioned photoacid generator D-1, 3.0 parts by weight The above polymer M-1 4.0 parts by weight The above-mentioned orientation control agent A-1, 1.9 parts by weight The above leveling agent L-1, 0.8 parts by weight 0.2 parts by weight of diisopropylethylamine 93.8 parts by weight of methyl ethyl ketone 372.0 parts by weight of methyl isobutyl ketone ―――――――――――――――――――――――――――――――― (Making of the A-plate (7B)) A positive A plate (7B) formed on the TAC thin film A-1 was fabricated using the same method as that described in Example 1 of International Publication No. 2020-050305. The positive A plate (7B) has a thickness of 2.5 μm and an in-plane retardation of 144 nm at a wavelength of 550 nm.

[0260] (Fabrication of polarizer (P7)) After corona treatment of the surfaces of the prepared positive C plate (7A) and positive A plate (7B), they were bonded together using the above-described UV-curable adhesive composition (1). After peeling off the support on the side of positive A plate (7B), corona treatment was performed on the peeled surface, and a polarizer was bonded to one side using the same method as in Example 3. An adhesive layer formed on the diaphragm was bonded to the surface of the cellulose acylate film (1), and a polarizer (P7) with an adhesive layer was produced.

[0261] At this time, the laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), adhesive layer (adhesive layer formed by curing ultraviolet curable adhesive composition, thickness 1μm), positive A plate (7B), adhesive layer (adhesive layer formed by curing ultraviolet curable adhesive composition, thickness 1μm), positive C plate (7A) (vertical alignment liquid crystal layer (7A), cellulose acylate film (1)), adhesive layer and diaphragm are stacked in sequence, and the angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (7B) is 45°.

[0262] <Comparative Example 3> (Fabrication of the positive C board (8A)) By changing polymer M-1 of the vertically aligned liquid crystal layer forming composition (7A) to polymer M-2, a vertically aligned liquid crystal layer forming composition (8A) was prepared. The vertically aligned liquid crystal layer forming composition (7A) was changed to the vertically aligned liquid crystal layer forming composition (8A), but otherwise, the prepared vertically aligned liquid crystal layer (8A) was bonded to a positive A plate (7B) using the same method as in Example 5. After peeling off the support of the positive A plate (7B), a UV-curable adhesive was used to bond it to a single-sided polarizer. Next, after peeling off the support (cellulose acylated film (1)) on the vertically aligned liquid crystal layer (8A) side, an adhesive layer formed on the aforementioned diaphragm was bonded, and a polarizer (P8) with an adhesive layer was prepared.

[0263] At this time, the laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), adhesive layer (adhesive layer formed by curing ultraviolet curable adhesive composition, thickness 1μm), positive A plate (7B), adhesive layer (adhesive layer formed by curing ultraviolet curable adhesive composition, thickness 1μm), vertically aligned liquid crystal layer (8A), adhesive layer and separator are stacked in sequence, and the angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (7B) is 45°.

[0264] <Example 6> By changing the leveling agent L-1 in the horizontally aligned liquid crystal layer forming composition (1B) to the leveling agent L-2 described below, a polarizer (P9) with an adhesive layer was produced by the same method as the polarizer (P1) of Example 1.

[0265] Leveling agent L-2 (The values ​​listed in the repeating units indicate the content (mass%) of each repeating unit relative to all repeating units. Weight-average molecular weight is 28,500.) [Chemical Formula 21] <Example 7> (Fabrication of polarizer (P10)) The polarizer protective film (1) was bonded to both sides of the polarizer (1) using a PVA adhesive to create a double-sided protective polarizer (2). Then, a laminated film consisting of a 50 μm thick PET film with a weak adhesive was bonded to the polarizer protective film (1). Next, after corona treatment of the coated surface of the laminated film (1) and one side of the double-sided protective polarizer (2), the two films were bonded together using the UV-curable adhesive composition (1) to ensure parallel length directions, and then irradiated with UV light (600 mJ / cm²). 2After curing, a polarizer with an adhesive layer (P10) was made.

[0266] At this time, the following are stacked in sequence: laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), PVA adhesive layer (thickness 0.2μm), polarizer protective film (1), adhesive layer (adhesive layer formed by curing UV-curable adhesive composition, thickness 1μm), positive A plate (1B), positive C plate (1A) (vertically aligned liquid crystal layer (1A), cellulose acylate film (1)), adhesive layer and diaphragm, the angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (1B) is 45°.

[0267] <Comparative Example 4> A photo-alignment film and a liquid crystal layer are formed on a cellulose acylated film using the method described in Example 1 of International Publication No. 2019-111880, serving as a positive A plate (11B).

[0268] After corona treatment of the coated surface of the positive A plate (11B), the composition for forming a curable resin layer described in paragraph 0211 of Japanese Patent Application Publication No. 2019-139219 is applied. After drying at 50°C for 1 minute, it is irradiated with a high-pressure mercury lamp (cumulative light intensity at a wavelength of 365nm under a nitrogen atmosphere: 400mJ / cm). 2 Ultraviolet light was used to form a cured resin layer with a thickness of 2.0 μm. The obtained cured resin layer was used as an alignment film, and the following vertical alignment liquid crystal layer forming composition (11A) was coated onto it to form a composition layer. The film with the composition layer formed was heated at 60°C for 1 minute with warm air, and while being purged with nitrogen to achieve an oxygen concentration of less than 100 ppm by volume, it was irradiated with a 365 nm UV-LED at an irradiation dose of 100 mJ / cm². 2 The ultraviolet light was then used to anneal the obtained coating at 130°C for 1 minute with warm air, thereby forming a positive C-plate (11A) with a thickness of 0.7 μm consisting of a vertically aligned liquid crystal layer (11A) with a thickness of 0.7 μm, and a laminated film (11) was produced.

[0269] ―――――――――――――――――――――――――――――――― Composition for forming a vertically aligned liquid crystal layer (11A) ―――――――――――――――――――――――――――――――― 100 parts by mass of the above-mentioned rod-shaped liquid crystal compound (A) Polymerizable monomer (A-400, manufactured by SHIN-NAKAMURA CHEMICAL CO, LTD.) 4.2 parts by weight The above-mentioned polymerization initiator S-1 (oxime type) 5.1 parts by weight The above-mentioned orientation control agent A-1, 1.9 parts by weight The above leveling agent L-1 0.5 parts by weight 0.2 parts by weight of diisopropylethylamine 466 parts by weight of methyl ethyl ketone ―――――――――――――――――――――――――――――――― After a laminated film consisting of a PET film with a weak adhesive and a thickness of 50 μm is bonded to the polarizer protective film (1) side of the single-sided polarizer (1), corona treatment is performed on the polarizer side surface and the cellulose acylate film surface of the laminated film (11), and then the above-mentioned UV-curable adhesive is used for bonding. Finally, an adhesive layer formed on the diaphragm is bonded to the surface of the vertically aligned liquid crystal layer (11A), thereby producing a polarizer (P11) with an adhesive layer.

[0270] At this time, the laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), adhesive layer (adhesive layer made by curing UV-curable adhesive composition, thickness 1μm), cellulose acylate film, positive A plate (11B), cured resin layer, vertically aligned liquid crystal layer (11A), adhesive layer and diaphragm are stacked in sequence, and the angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (11B) is 45°.

[0271] <Example 8> After fabricating the positive C plate (7A) by the method described in Example 5, a corona treatment was performed on the surface of the vertically aligned liquid crystal layer (7A), and a horizontally aligned film and a horizontally aligned liquid crystal curing film were fabricated by the method described in paragraph 0214 of Japanese Patent Application Publication No. 2019-139219. The horizontally aligned liquid crystal curing film was used as the positive A plate (12B) to obtain a laminated film (12).

[0272] In addition, the in-plane delay of the positive A plate (12B) is 142nm at a wavelength of 550nm.

[0273] A laminated film (12) was used instead of a laminated film (3), and a polarizer with an adhesive layer (P12) was otherwise made in the same manner as in Example 5.

[0274] At this time, the laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), adhesive layer (adhesive layer made by curing UV-curable adhesive composition, thickness 1μm), positive A plate (12B), horizontal alignment film, vertical alignment liquid crystal layer (7A), cellulose acylate film (1), adhesive layer and diaphragm are stacked in sequence, and the angle between the absorption axis of polarizer (1) and the in-plane slow axis of positive A plate (12B) is 45°.

[0275] <Example 9> A laminated film (13) consisting of a substrate, a cured resin layer, a vertically aligned liquid crystal layer (equivalent to the vertically aligned liquid crystal cured film of Japanese Patent Application Publication No. 2019-139219), a horizontally aligned film, and a horizontally aligned liquid crystal layer was prepared by the method described in paragraphs 0202 to 0215 of Japanese Patent Application Publication No. 2019-139219. The laminated film (13) was used instead of the laminated film (3), and a polarizer (P13) with an adhesive layer was prepared by the same method as in Example 5.

[0276] At this time, the laminated film, polarizer protective film (1), PVA adhesive layer (thickness 0.2μm), polarizer (1), adhesive layer (adhesive layer made by curing UV-curable adhesive composition, thickness 1μm), horizontally aligned liquid crystal layer (equivalent to positive A plate), horizontally aligned film, positive C plate (vertically aligned liquid crystal layer, cured resin layer, substrate (TAC film)), adhesive layer and separator are stacked in sequence, and the angle between the absorption axis of polarizer (1) and the in-plane slow axis of horizontally aligned liquid crystal layer is 45°.

[0277] The positive C-plate is configured to include the above-mentioned vertically oriented liquid crystal layer, cured resin layer and substrate. The positive C-plate has an in-plane retardation of 0 nm at a wavelength of 550 nm and a thickness direction retardation of -70 nm at a wavelength of 550 nm.

[0278] Furthermore, the thickness of the vertically aligned liquid crystal layer is 0.7 μm, and the thickness of the substrate (TAC film) is 40.0 μm.

[0279] In addition, the horizontally aligned liquid crystal layer (equivalent to the front A plate) has an in-plane retardation of 141 nm at a wavelength of 550 nm.

[0280] <Example 10> The thickness of the adhesive layer (the adhesive layer formed on the diaphragm) described in Example 1 was changed from 20 μm to 40 μm. Otherwise, a polarizer with adhesive (P14) was made in the same manner as in Example 1.

[0281] <Example 11> The thickness of the adhesive layer (the adhesive layer formed on the diaphragm) described in Example 1 was changed from 20 μm to 10 μm. Otherwise, a polarizer with adhesive (P15) was made in the same manner as in Example 1.

[0282] <Determination of Optical Properties> Using an AxoScan OPMF-1 (manufactured by OptScience Co., Ltd.), the light incident angle dependence of Re and the tilt angle of the optical axis (i.e., the tilt of the direction of maximum refractive index of the optical anisotropic layer relative to the aforementioned optical anisotropic layer) were measured at a wavelength of 550 nm. The in-plane retardation Re and the thickness direction retardation Rth of the optical anisotropic layer at a wavelength of 550 nm were then calculated.

[0283] <Film Thickness Measurement of Laminated Thin Films> The thickness of the laminated film was measured using a contact film thickness gauge.

[0284] <Measuring the film thickness of the liquid crystal layer> The thickness of the liquid crystal layer was measured using a reflective spectrophotometer FE3000 (manufactured by Otsuka Electronics Co., Ltd.).

[0285] <Film Thickness Measurement of Laminated Thin Films and Polymer Thin Films> The thicknesses of laminated films and polymer films were measured using a contact film thickness gauge.

[0286] <Fitness Assessment> The fabricated polarizer with adhesive layer was cut into strips of 30mm × 120mm, and the diaphragm on the adhesive layer side was peeled off. After the exposed adhesive layer was bonded to the glass, the laminate film on the opposite side was peeled off. Eleven slits were cut at 1mm intervals from the surface of the polarizer to the depth of the adhesive bonded to the glass, and another eleven slits were cut in the same orthogonal direction, thus forming 100 grids. Adhesive tape (polyester adhesive tape NO.31B, manufactured by Nitto Denko Corporation) was applied to the grid, and the tape was peeled off at an angle of approximately 60°. The number of grids peeled off was counted, and the results were evaluated according to the following criteria.

[0287] A: The number of cells stripped is less than 50. B: The number of cells stripped is 51 or more. <Assessment of processing suitability (curl)> The polarizers with adhesive layers obtained in each embodiment and comparative example were cut into 200mm × 200mm sizes with the MD direction as the diagonal, and the separator was peeled off to prepare samples. Next, the obtained samples were placed at 25°C and 60% humidity for more than 3 hours, and then placed on a glass substrate with the peeled side facing up, and evaluated as follows. The higher the value of A, the more the curling of the polarizer with adhesive layer is suppressed.

[0288] A: The polarizer is lifted less than 10mm from the substrate, making it easy to attach.

[0289] B: The polarizer is lifted from the substrate by more than 10mm but less than 20mm, and can be bonded.

[0290] C: The polarizer is lifted from the substrate by more than 20mm but less than 30mm, allowing for proper bonding.

[0291] D: The polarizer floats more than 30mm off the substrate, making it difficult to bond.

[0292] <Reprocessing Assessment> The cover glass and polarizer were peeled off from a commercially available Galaxy A1 smartphone (manufactured by Samsung Electronics Co., Ltd.) to expose the glass on the OLED substrate surface. The polarizer with adhesive layer prepared above was cut to the same size as the smartphone, the separator was peeled off, and it was then rolled onto the glass surface of the OLED substrate. After the obtained sample was placed at 25°C and 60% humidity for 24 hours, the polarizer with adhesive layer was carefully peeled off, and its reprocessability was evaluated according to the following criteria.

[0293] A: Nothing remained on the glass, allowing for clean peeling.

[0294] B: Some of the adhesive and liquid crystal curing film remain on the glass. If you try to remove them, the glass will break, so they cannot be removed.

[0295] In Table 1, the column “Positive C film thickness (μm)” indicates the film thickness (μm) of the positive C plate.

[0296] In Table 1, the "Adhesive" column indicates the type of adhesive layer disposed between the polarizer and the positive A plate. "PVA adhesive" indicates polyvinyl alcohol-based adhesive, and "UV adhesive" indicates an adhesive layer formed by curing an ultraviolet-cured adhesive.

[0297] In Table 1, the "Crosslinked Polymer" column indicates whether the vertically aligned liquid crystal layer contains cured crosslinked polymers, with "A" indicating inclusion and "B" indicating absence. Furthermore, in cases evaluated as "A", the cured crosslinked polymers in the vertically aligned liquid crystal layer are biased towards the cellulose acylate film (polymer film) side present in the positive C-plate.

[0298] In Table 1, the "Photoisomerization compound" column indicates whether the vertically aligned liquid crystal layer contains a photoisomerization compound, with "A" indicating its presence and "B" indicating its absence. Furthermore, in cases evaluated as "A", the photoisomerization compound in the vertically aligned liquid crystal layer is present on the surface of the positive C-plate opposite to the cellulose acylate film (polymer film) side.

[0299] In Table 1, the column “Formula (1)” indicates whether the positive A plate contains a polymer having a group represented by the above formula (1), “A” indicates that it contains, and “B” indicates that it does not contain.

[0300] [Table 1]

[0301] As shown in the table above, the polarizer with adhesive layer of the present invention exhibits the desired effect.

[0302] Furthermore, through a comparison of Examples 3 and 4, it was confirmed that the effect was better when the cured product containing the cross-linked polymer was included in the vertically oriented liquid crystal layer.

[0303] Furthermore, through a comparison of Examples 1 and 6, it was confirmed that the effect was better when the positive A plate contained a polymer having a group represented by the above formula (1).

[0304] Furthermore, through comparison of Examples 5, 8, and 9 with other examples, it was confirmed that the effect is even better when the vertically aligned liquid crystal layer contains a photoisomerization compound (when the positive A plate and the positive C plate are in direct contact).

[0305] Furthermore, through comparison of Example 9 with other examples, it was confirmed that the effect is better when the vertically aligned liquid crystal layer is in direct contact with the polymer film.

[0306] <Confirmation of Area A and Area B> In Examples 1-11, it was confirmed that the polymer film contained a region (designated as region A) containing components derived from the liquid crystal compound contained in the vertically aligned liquid crystal layer, and that the vertically aligned liquid crystal layer contained components derived from the liquid crystal compound contained in the positive A plate, were present. When a region was confirmed to be present, the thickness of the region containing the liquid crystal compound was measured. It was confirmed that the thickness of region A was in the range of 20-200 nm, and the thickness of region B was in the range of 5-100 nm.

[0307] Symbol Explanation 10-Polarizer with adhesive layer, 12-Polarizer, 14-Protective film, 16-Polarizer, 18-Positive A plate, 20-Positive C plate, 22-Adhesive layer, 24-Vertically aligned liquid crystal layer, 26-Polymer film.

Claims

1. A polarizer with an adhesive layer, comprising: A polarizer, comprising a protective film, a polarizer, a positive A plate, and a positive C plate, in sequence; and An adhesive layer is disposed on the positive C-plate side of the polarizer, wherein, The positive A plate is a layer obtained by curing a polymerizable liquid crystal compound, and the thickness of the positive C plate is 20.0 to 70.0 μm.

2. The polarizer with adhesive layer according to claim 1, wherein, When the polarizer with adhesive layer is bonded to the glass substrate via the adhesive, and a cross-cut test of 100 grids is performed on the bonded polarizer with adhesive layer, the number of grids peeled off is less than 50.

3. The polarizer with adhesive layer according to claim 1, wherein, The thickness retardation of the positive C plate at a wavelength of 550 nm is -100 to -30 nm.

4. The polarizer with adhesive layer according to claim 1, wherein, The positive C plate contains a polymer film.

5. The polarizer with adhesive layer according to claim 4, wherein, The polymer film is a cellulose acylated film.

6. The polarizer with adhesive layer according to claim 4, wherein, The polymer film has an in-plane retardation of less than 10 nm at a wavelength of 550 nm.

7. The polarizer with adhesive layer according to claim 4, wherein, The polymer film has a thickness retardation of -100 to 30 nm at a wavelength of 550 nm.

8. The polarizer with adhesive layer according to claim 4, wherein, The positive C-plate comprises a vertically oriented liquid crystal layer and the polymer film.

9. The polarizer with adhesive layer according to claim 8, wherein, The vertically oriented liquid crystal layer contains crosslinks that are biased toward the side of the polymer film.

10. The polarizer with adhesive layer according to claim 8, wherein, The vertically oriented liquid crystal layer is a layer formed using a composition comprising a liquid crystal compound and a crosslinking polymer, wherein the crosslinking polymer has hydroxyl groups.

11. The polarizer with adhesive layer according to claim 8, wherein, The vertically oriented liquid crystal layer contains a photoisomerizing compound on the surface opposite to the polymer film side.

12. The polarizer with adhesive layer according to claim 1, wherein, The angle between the absorption axis of the polarizer and the in-plane slow axis of the positive A plate is 45±10°. The in-plane delay of the positive A plate at a wavelength of 550 nm is 120–170 nm.

13. The polarizer with an adhesive layer according to claim 1, wherein, The polarizer and the positive A plate are laminated together using a polyvinyl alcohol adhesive.

14. The polarizer with an adhesive layer according to claim 1, wherein, The positive A plate is a layer obtained by curing a composition comprising a polymeric liquid crystal compound and a polymer having groups represented by formula (1). Formula (1) -B-(OR x1 )2 R x1 Each of the two R groups independently represents a hydrogen atom, a substituted or unsubstituted aliphatic hydrocarbon group, a substituted or unsubstituted aryl group, or a substituted or unsubstituted heteroaryl group. x1 They can be linked together via alkylene linkages, arylene linkages, or combinations thereof.

15. The polarizer with adhesive layer according to claim 1, wherein, The polarizer and the positive A plate are stacked together via an adhesive layer, which is formed by curing an ultraviolet-curable adhesive.

16. The polarizer with adhesive layer according to claim 8, wherein, The polymer film includes region A, which contains components derived from the liquid crystal compound contained in the vertically aligned liquid crystal layer, and the thickness of region A is 20–200 nm.

17. A display device having a polarizer with an adhesive layer as claimed in any one of claims 1 to 16.

Citation Information

Patent Citations

  • Engine cover of combine

    JP1990020215A

  • polymerizable liquid crystal compound

    JP1999513019A

  • Liquid crystal compound, liquid crystyal composition, polymer, retardation plate, and elliptical polarization plate

    JP2005289980A

  • Laminate and method for manufacturing the same

    JP2019139219A

  • Polarizer having adhesive layer

    JP2023126297A